Comparative study between fully tethered and free swimming at different paces of swimming in front crawl. Issue 6 (2nd November 2019) - Samson, Mathias; Monnet, Tony; Bernard, Anthony; Lacouture, Patrick; David, Laurent
Abstract: Tethered swimming is a method often used to measure or enhance the physical and technical resources of swimmers. Although it is highlighted that the technique used in tethered swimming is probably different from that used in free conditions, there are few comparative studies on this subject. The current study aims to compare fully tethered and free swimming based on kinematic hand parameters (orientation, velocity and acceleration of the hand, sweepback and angle of attack), which are known to act directly on the generation of propulsive forces. The results show that there are significant differences during the stretch and catch phases but less during the insweep and upsweep phases. Tethered swimming makes it possible to estimate the propelling forces generated by the hand in free swimming at distance and middle-distance paces, but overestimates it at sprint pace. However, in view of the modifications of the kinematic parameters, it should not be used under repeated conditions of use, such as for the development of swimmers' capacity.